Alteration in the physical-water attributes of an Entisols under conventional and organic management - Aires, Eduardo Santana [UNESP] (2019)
Soil management systems are designed to create favorable conditions for the development of crops, and can modify the physical and water characteristics of the soil. Therefore, the objective of the research was to determine the physical-hydric characteristics of a soil under different land use and management systems. The study was carried out at the Universidade do Estado da Bahia - UNEB, the study area has soil classified as Entisols under two types of management, organic and conventional, using a completely randomized design with four treatments: Banana cultivation under organic (T1) and conventional (T2) management and tomato under organic (T3) and conventional (T4) management, in 5 repetitions. The following soil attributes were evaluated: basic infiltration speed (VIB), soil (ds) and particle density (dp), total porosity (Pt), micro (MIP) and macroporosity (MAP), organic matter content (MO) and carbon stock (EC). In cultivated with banana and under organic soil management it is observed that the values of macroporosity, M.O. and the carbon stock are 233.77% and 205%, 194% higher, respectively, than when compared to the banana area under conventional soil management. Banana cultivation under organic soil management showed higher values of VIB and total porosity, and lower values of soil density. When comparing the areas cultivated with tomatoes under different management, it appears that the DP, PT and MIP were higher in organic areas (2.29 g cm; 45.84% and 32.66%) than in the conventional area (2.11 g cm; 38.08% and 32.66%). Microporosity did not vary depending on the management and / or use of the soil, despite differences in the means of treatments (conventional bananas and organic tomatoes). The infiltration of water was easier in under cultivated with tomato and banana under organic management. Different crops and soil management promote changes in the physical-hydric characteristics of the Entisols.